Research on ciphertext search for the cloud environment - Fei XIANG; Chuan-yi LIU; Bin-xing FANG; Chun-lu WANG; HONGRui-ming Z (Tongxin xuebao)
In order to ensure the data privacy, users have to encrypt the data before outsourcing them to the cloud, How-ever, the encrypted data cannot take full advantage of the rich service function and powerful computation ability of the cloud platform. Ciphertext search technology can combine the protection of user data's privacy with the efficient usage of cloud platform services. On the basis of analyzing the ciphertext search technologies in cloud computing environment, a ciphertext search system architecture based on cloud c g environment was proposed and the key technologies of ciphertext search were studied. Finally the ciphertext search technologies' main problems at present and the important re-search direction in future were pointed out.